2015
DOI: 10.1007/s10308-015-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

Normative Power Europe meets the Israeli-Palestinian conflict

Abstract: The article examines the European Union's (EU) normative position regarding the Israeli-Palestinian conflict to advance three interrelated claims. First, that EU member states subscribe to a unified normative position because the normative sphere is cut off from the economic sphere. Second, that this separation facilitates the uniformity of the normative position but hinders the possibility of asserting some form of conditionality which might encourage the diffusion of Ian Manners' five core norms. Finally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Israeli scholars Pardo and Harpaz with their respective colleagues have begun to close this gap by connecting NPE to Israeli perceptions of the EU. Their main conclusions, some of which this article will disagree with, are that there is no evidence of Manners' five core norms being diffused (Gordon and Pardo, , p. 266; Pardo, , p. 99), that the EU suffers from a legitimacy deficit vis‐à‐vis Israel, which affects its normative power negatively (Harpaz and Shamis, , p. 580), that the EU is high on rhetoric and low on delivery (Harpaz and Shamis, , p. 604, see also Tocci, , p. 387), that the normative sphere is cut off from the economic sphere (Gordon and Pardo, , p. 271) and that the EU's normative power is determined to a certain extent by the resistance that it encounters (Gordon and Pardo, , p. 417).…”
Section: Npe In the Eyes Of Others Outside The Eumentioning
confidence: 92%
See 2 more Smart Citations
“…Israeli scholars Pardo and Harpaz with their respective colleagues have begun to close this gap by connecting NPE to Israeli perceptions of the EU. Their main conclusions, some of which this article will disagree with, are that there is no evidence of Manners' five core norms being diffused (Gordon and Pardo, , p. 266; Pardo, , p. 99), that the EU suffers from a legitimacy deficit vis‐à‐vis Israel, which affects its normative power negatively (Harpaz and Shamis, , p. 580), that the EU is high on rhetoric and low on delivery (Harpaz and Shamis, , p. 604, see also Tocci, , p. 387), that the normative sphere is cut off from the economic sphere (Gordon and Pardo, , p. 271) and that the EU's normative power is determined to a certain extent by the resistance that it encounters (Gordon and Pardo, , p. 417).…”
Section: Npe In the Eyes Of Others Outside The Eumentioning
confidence: 92%
“…This probably makes the Israeli–Palestinian conflict one of the longest, sustained cases of active EC/EU involvement in world politics, and thus a prime test ground for Normative Power Europe (NPE), originally developed by Ian Manners in 2002. A number of researchers, led by the Israeli scholars Sharon Pardo and Guy Harpaz have in their works concluded that the EU – at best – has displayed limited normative power in the Israeli–Palestinian conflict (Bouris, , p. 80; Del Sarto, , p. 213; Diez and Pace, , p. 220; Gordon and Pardo, , p. 266; Gordon and Pardo, , p. 424; Harpaz, , p. 89; Harpaz and Shamis, , p. 587; Huber, , p. 1; Pardo, , p. 99; Pardo and Peters, , p. 115). This, in turn, taps in to a more general critique of the EU as a failed peacebuilder in the conflict (See, for example Bouris, , p, 175; Keukeleire and MacNaughtan, , p. 284; Miller, , p. 194; Pace, , p. 610).…”
Section: What Is Wrong With the Field Of Normative Power Europe (Npe)mentioning
confidence: 99%
See 1 more Smart Citation
“…The European Union (EU) is frequently described as a normative power in peacebuilding that projects its own experience, norms, and values as a liberal peace project externally (Tocci 2008, Diez and Pace 2011, Richmond et al 2011. The projection of the EU's normative power in peacebuilding has been particularly pronounced in the case of the Israeli-Palestinian conflict (Harpaz 2007, Gordon and Pardo 2015, Persson 2017. The Israeli-Palestinian conflict constitutes a longstanding priority of the EU's foreign policy agenda that has been reaffirmed in the EU's Global Strategy of 2016 and the EU has dedicated considerable time and resources to address the conflict (Pardo and Peters 2009, Musu 2010, Müller 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The narrative lens is also sensitive to the view that the EU's normative power evolves in interaction with others, who receive and interpreted it through their own cultural filters (Kinnvall 1995;Manners 2002, Gordon and Pardo 2015, p. 416, Chaban et al 2017, p. 1274, Malone et al 2017. As observers have noted, European narratives are created, reproduced, upheld, justified and legitimised (Manners 2013, pp.…”
Section: Introductionmentioning
confidence: 99%